2013
DOI: 10.1159/000351651
|View full text |Cite
|
Sign up to set email alerts
|

Triple Therapy for Anti-Vascular Endothelial Growth Factor Nonresponders in Neovascular Age-Related Macular Degeneration: Impact of Different Photodynamic Therapy Parameters

Abstract: Purpose: To evaluate the safety and exploratory efficacy of triple therapy (TT) with single-session intravitreal ranibizumab, modified juxtascleral triamcinolone, and photodynamic therapy (PDT) in exudative age-related macular degeneration non-responder to anti-vascular endothelial growth factor. Methods: Thirty consecutive eyes were included. The first 10 eyes (cohort 1) enrolled received same-day TT with reduced-fluence/reduced-irradiance PDT, 10 eyes (cohort 2) received same-day TT with reduced-fluence/stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Often combined with other chemotherapy, it improves response and survival in certain cancer types, including advanced cervical cancer [6]. Given the inhibitory effects on neovascularization, intraocular diseases associated with the formation of new vessels, such as age-related macular degeneration and diabetic retinopathy, may also benefit from bevacizumab intervention [7]. In addition to bevacizumab, there are many other drugs that target the VEGF pathway and angiogenesis, including other VEGF ligands, VEGFR blockers, and tyrosine kinase inhibitors, such as sunitinib and sorafenib, that block VEGF-induced cellular signaling [8].…”
Section: Discussionmentioning
confidence: 99%
“…Often combined with other chemotherapy, it improves response and survival in certain cancer types, including advanced cervical cancer [6]. Given the inhibitory effects on neovascularization, intraocular diseases associated with the formation of new vessels, such as age-related macular degeneration and diabetic retinopathy, may also benefit from bevacizumab intervention [7]. In addition to bevacizumab, there are many other drugs that target the VEGF pathway and angiogenesis, including other VEGF ligands, VEGFR blockers, and tyrosine kinase inhibitors, such as sunitinib and sorafenib, that block VEGF-induced cellular signaling [8].…”
Section: Discussionmentioning
confidence: 99%
“…It found that both standard fluence and standard irradiance produced visual decline at 6 months (change of 0.29 logMAR, p < 0.05), possibly due to choroidal ischaemia. Reduced fluence/standard irradiance and reduced fluence/reduced irradiance were associated with no significant visual change (Veritti & Lanzetta ). Single dosage combination intravitreal triamcinolone, intravitreal bevacizumab and oscillatory thermotherapy in conjunction with ICGA for resistant nAMD has been evaluated in one series.…”
Section: Methodsmentioning
confidence: 99%
“…10 “Triple therapy,” in which patients with AMD receive intravitreal dexamethasone or triamcinolone acetonide injections, intravitreal bevacizumab or other anti-VEGF injections, and photodynamic therapy, has been described to stabilize and sometimes improve VA in eyes with neovascular AMD that does not respond to anti-VEGF treatment alone. 11,12…”
Section: Resultsmentioning
confidence: 99%